Prioritizing social determinants of health in East Azerbaijan: a qualitative research - Laghousil, Delara; Abbaszadeh, Mohammad; Alizadeh, Mahasti; Mohammad pour, Nayyereh; Boudaghi, Ali (Social Determinants of Health, 2020)
Background: In order to improve health-centered decision making and planning to reduce inequalities in health, it is important to identify, classify, and prioritize social determinants of health. This study aimed to identify and rank three major social determinants of health in East Azerbaijan. Methods: This research was conducted using a qualitative approach in grounded theory. Through purposeful sampling, 40 key informants from East Azerbaijan, North West of Iran, were selected and in-depth interviews were performed. The collected data was analyzed with a three-step coding method including open, axial, and selective coding using Corbin and Strauss’s systemic approach. Also, Interpretive Structural Modeling and “Matrice d'Impacts Croisés Multiplication Appliquée à un Classement” (MICMAC) analysis were used to identify and rank social determinants of health in East Azerbaijan. Results: Of the 40 participants, 27 (68%) were male and 13 (32%) were female. The mean age was 39.28± 12.46 years. 63% had a doctoral degree. According to the result of MICMAC analysis, social harm, social capital, and good governance were identified as three major social determinants of health in East Azerbaijan province. Conclusion: Social determinants of health have a significant and crucial role in human welfare and by identifying and prioritizing social determinants of health at a local level and/or national level, the first step can be taken toward social welfare.